Trichilemmal Cyst of the Eyelid: Masquerading as Recurrent Chalazion - Manju Meena; Ruchi Mittal; Debarati Saha (Case Reports in Ophthalmological Medicine)
A 52-years-old female presented with a history of a painless, progressive swelling in the left lower eyelid of one-year duration. The lesion was excised twice as a chalazion and recurred. Excisional biopsy of the mass was performed and histopathological findings were consistent with those of trichilemmal cyst. We report a rare case of trichilemmal cyst of the eyelid which was masquerading as chalazion for which the patient had undergone multiple surgeries. Wide excision was done and diagnosis was confirmed on histopathology. There was no recurrence seen till 2 months of postoperative period. Trichilemmal cyst, although rare, should be considered as differential diagnosis of recurrent chalazion.